Statistical interpretation of carbon dioxide emission in the photocopying process - Kiurski Jelena; Oros Ivana; Kecić Vesna; Aksentijević Snežana; International Symposium on Analytical and Environmental Problems (21.) (2015) (Szeged) (2015)
The concentration levels of carbon dioxide, monitored in indoor of three photocopying shops in Novi Sad, Serbia, were subjected to two-way ANOVA, in order to investigate statistically significant emission, due to the different sampling points and time intervals. Obtained results pointed out that only selection of time interval significantly affects the emission of carbon dioxide. In addition, the least significant difference test indicated that second time interval has the greatest influence on the CO2 emission, whereas the CO2 concentrations of the second time interval were subjected to further cluster analysis. Hierarchical clustering grouped three photocopying shops into four clusters with similar CO2 concentration levels.